1,25-Dihydroxyvitamin D(3) and prostaglandin E(2) act directly on circulating human osteoclast precursors. - Itonaga, I; Sabokbar, A; Neale, S; Athanasou, N (1999)
1,25-Dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) and prostaglandin E(2) (PGE(2)) are known to influence osteoclast formation indirectly through their effects on osteoblasts. To determine whether 1, 25(OH)(2)D(3) and PGE(2) also have a direct effect on circulating osteoclast precursors, these factors were added to long-term cultures of human peripheral blood mononuclear cells (PBMCs) in the presence of osteoprotegerin ligand and macrophage colony-stimulating factor (M-CSF) (+/-dexamethasone). The number of TRAP(+) and VNR(+) multinucleated cells and the area of lacunar resorption were decreased when 1,25(OH)(2)D(3) alone was added. A marked increase in resorption pit formation was noted when the combination of 1, 25(OH)(2)D(3) and dexamethasone was added to PBMC cultures. Dose-dependent inhibition of osteoclast formation and lacunar resorption was seen when PGE(2) was added to PBMC cultures in both the presence and the absence of dexamethasone. Thus, 1,25(OH)(2)D(3) and PGE(2) not only influence osteoclast formation in the presence of bone stromal cells but also act directly on circulating osteoclast precursors to influence osteoclast differentiation.